Inspiring Early Childhood Education: Fostering Creativity and Innovation - Alfiansyah, Alfiansyah; Nusantara Putri, Sari (LP2M IAI Al-Khairat Pamekasan, 2024)
Inspiring Early Childhood Education (ECE) plays a crucial role in shaping children's character and foundational skills. One of the key approaches in this education is fostering creativity and innovation from an early age. Through a supportive learning environment, play-based learning methods, and parental involvement, children can develop critical thinking, problem-solving, and creativity skills that will benefit them throughout their lives. This study aims to explore various strategies that can be implemented to encourage creativity and innovation in ECE, as well as the positive impacts it has on children's development. The research findings indicate that education emphasizing creativity and innovation not only enhances children's self-confidence but also helps them become adaptive, empathetic individuals capable of facing future challenges.